ANALYTICAL SYNTHESIS OF THE METHOD OF TARGETING A SUPERSONIC UNMANNED AERIAL VECHICLE BASED ON MULTI-DIMENSIONAL NONLINEAR DYNAMIC MODEL - V. E. Markevich (Informatika)
A method of analytical synthesis of an optimal controller for the terminal control task of supersonic unmanned aerial vehicles based on synergetic approach to the design of control systems for nonlinear multidimensional dynamic objects is considered.The article provides analytical expressions describing the algorithm for control the velocity vector position of a supersonic UAV, the simulation results and the comparative analysis of the proposed control algorithm with the modified method of proportional navigation.